University Students' Perceptions of AI-Assisted Writing Tools in Supporting Self-Regulated Writing Practices - Amani, Nailatul; Bisriyah, Maslihatul (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Artificial intelligence (AI) is transforming education by offering personalized learning tools, yet its role in fostering self-regulated learning (SRL) strategies among English as a Foreign Language (EFL) students remains underexplored. This study investigates EFL students' perceptions of AI applications in supporting their self-regulated writing strategies, particularly in planning, monitoring, and evaluation. Employing a qualitative case study approach, data were collected from 40 EFL students at an Islamic-based university in East Java, Indonesia, through questionnaires, semi-structured interviews, and document analysis. The findings indicate that most students perceive AI tools as beneficial, particularly for grammar checking, spelling correction, and word choice improvement, though their reliance on AI for idea generation, topic selection, and writing progress monitoring varies. While AI is valued for feedback, paraphrasing, and translation, students still prefer human guidance for in-depth explanations, with some expressing concerns that excessive dependence on AI may hinder their comprehension and writing confidence. These findings highlight the need for a balanced integration of AI tools into writing instruction, emphasizing the importance of human feedback and personalized learning approaches.